5z-z+3=

Simple and best practice solution for 5z-z+3= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5z-z+3= equation:


Simplifying
5z + -1z + 3 = 0

Reorder the terms:
3 + 5z + -1z = 0

Combine like terms: 5z + -1z = 4z
3 + 4z = 0

Solving
3 + 4z = 0

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + 4z = 0 + -3

Combine like terms: 3 + -3 = 0
0 + 4z = 0 + -3
4z = 0 + -3

Combine like terms: 0 + -3 = -3
4z = -3

Divide each side by '4'.
z = -0.75

Simplifying
z = -0.75

See similar equations:

| 4x+159=2x+153 | | 35-17=3x-6 | | -8-12=20 | | 18+3x-x^2=0 | | 33x-9=90 | | (-2w)(2w-3)(3w+10)=0 | | 4x^2-33x+48=-4x+3 | | 3(5c-3)-2=13c+1 | | 4x(2x+y)= | | 6x+21=90 | | 4x+17=-17 | | 8x^2+2n-15=0 | | m(4-m)(5+m)=0 | | y=12.8x+24 | | 11b+7=50 | | 16-x=16x+10 | | -6+[x-4]=-6 | | -5(x+4)=50 | | (4u-3)(u+1)=0 | | 4x^5-12x^4=0 | | 12x+12=x+7 | | 3x-36-180=x | | 12+56=6(t+12) | | f(x^2)=5-2x | | -7-13v=32 | | 1.5x=10x | | 3(c+5)=18 | | 6x-(x+4)=4(x-2) | | ax-B=Cynthia | | 8=[x-2.5] | | (3x+1)(4x-7)=0 | | -5h-3=-43 |

Equations solver categories